Optimizing the Tri-Center of Education as the Root of the Formation of an Islamic Educational Environment from a Hadith Perspective - Rikza Syahrial Kurniawan; Eferadina Salsabila Novariantry; Ananda Salsabiila Irham; Agus Alfaya Arif; Suyudi Suyudi (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This study discusses the three educational centers that are fully optimized in order to form an Islamic educational environment based on the hadith of the Prophet Muhammad SAW. The research method used is a qualitative approach with a type of library research. This approach was chosen because the research is focused on content analysis of hadiths related to the Islamic educational environment. Education in the Islamic view is not limited to formal institutions such as schools or madrasahs, but includes a wider space, including the family and community environment known as the three educational centers. This term was first introduced by Ki Hadjar Dewantara who stated that the educational process takes place through three main centers. These three elements form a complete educational ecosystem and are interrelated in the process of forming personality, character, and competence. Education is influenced by the environment which is the main foundation that forms the direction and pattern of education. The better a person's educational environment, the better the quality of their education.